Prime Minister Decree No. 1265/2014 Promulgating The Executive Regulations Of Decree-Law No. 63/2014 Of The Maximum Limit Of Incomes Of The State Bodies Wage Earners = قرار رئيس مجلس الوزراء رقم 1265 لسنة 2014 بالقواعد التنفيذية لأحكام القرار بقانون رقم 63 لسنة 2014 بشأن الحد الأقصى للدخول للعاملين بأجر لدى أجهزة ة الدولة. - Egypt; The middle east library for economic services, translator. (2025)
Prime minister decree no. 1265 of the year 2014 promulgating the executive regulations of decree law no. 63 of the year 2014 of the maximum limit of income of the state bodies wage-earners قرار رئيس مجلس الوزراء رقم 1265 لسنة 2014 بالقواعد التنفيذية لأحكام القرار بقانون رقم 63 لسنة 2014 بشأن الحد الأقصى للدخول للعاملين بأجر لدى أجهزة الدولة